Pengaruh Kepemimpinan Kepala Sekolah terhadap Motivasi Kinerja Guru dalam Meningkatkan Kualitas Pendidikan Agama Islam - Ferianto, Ferianto (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2022)
This study aims to analyze the Influence of Principal Leadership and Teacher Work Motivation on Teacher Performance in improving the Quality of Islamic Religious Education. Aspects that affect the quality of education include coaching programs for principals and teachers periodically, effectively and efficiently, socialization of programs as an effort to transform or socialize the program, and aspects of a comprehensive evaluation of all aspects of the implementation of the coaching and supervision program, to see and assess the extent of its successes and shortcomings in an effort to improve teacher performance to improve the quality of Islamic Religious Education.